Pengaruh Current Ratio, Debt To Assets Ratio, dan Sales Growth terhadap Financial Distress pada Perusahaan Sub-Sektor Otomotif dan Komponen Periode 2022-2024 - Tiffany Aurelia Taslim; Mutiara Maimunah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to examine the effect of Current Ratio (CR), Debt to Assets Ratio (DAR), and Sales Growth (SG) on Financial Distress in automotive and component sub-sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research is motivated by post-pandemic sales fluctuations and inconsistencies in prior findings. A quantitative explanatory associative method was employed, with a purposive sampling technique yielding 10 companies and 30 firm-year observations. Data were analyzed using multiple linear regression with a bootstrap approach due to the sample size limitations. The results show that simultaneously, CR, DAR, and SG significantly affect Financial Distress. Partially, Current Ratio and Sales Growth have no significant effect, while Debt to Assets Ratio has a significant negative effect. This finding indicates that increased debt usage during 2022–2024 correlates with better financial health, possibly because firms able to secure loans signal credibility to creditors. The implication is that liquidity and sales growth alone are not strong predictors of financial distress in the automotive industry, suggesting that management and investors should not rely solely on these ratios